Circadian clock components control daily growth activities by modulating cytokinin levels and cell division‐associated gene expression in Populus trees. (15th April 2018) - Edwards, Kieron D.; Takata, Naoki; Johansson, Mikael; Jurca, Manuela; Novák, Ondřej; Hényková, Eva; Liverani, Silvia; Kozarewa, Iwanka; Strnad, Miroslav; Millar, Andrew J.; Ljung, Karin; Eriksson, Maria E.
Abstract: Trees are carbon dioxide sinks and major producers of terrestrial biomass with distinct seasonal growth patterns. Circadian clocks enable the coordination of physiological and biochemical temporal activities, optimally regulating multiple traits including growth. To dissect the clock's role in growth, we analysed Populus tremula  ×  P. tremuloides trees with impaired clock function due to down‐regulation of central clock components. late elongated hypocotyl ( lhy‐10 ) trees, in which expression of LHY1 and LHY2 is reduced by RNAi, have a short free‐running period and show disrupted temporal regulation of gene expression and reduced growth, producing 30–40% less biomass than wild‐type trees. Genes important in growth regulation were expressed with an earlier phase in lhy‐10, and CYCLIN D3 expression was misaligned and arrhythmic. Levels of cytokinins were lower in lhy‐10 trees, which also showed a change in the time of peak expression of genes associated with cell division and growth. However, auxin levels were not altered in lhy‐10 trees, and the size of the lignification zone in the stem showed a relative increase. The reduced growth rate and anatomical features of lhy‐10 trees were mainly caused by misregulation of cell division, which may have resulted from impaired clock function. Abstract : Trees undergo annual cycles of significant primary and secondary growths. They possess an endogenous clock that enables them to adjust growth to different seasons. This study demonstrates the importance of the circa 24‐hr (circadian) clock in sustaining growth of Populus trees under diel cycles and shows the clock times expression of CYCD3 and cell division. Notably, growth hormones are disrupted in trees with broken clocks. The clock, acting via the key clock components, LHY1 and LHY2 regulates gene expression and protein function. Reducing expression of LHY1 and LHY2 reduces levels of cytokinins, which regulate plant growth, and causes a misalignment of CYCD3 expression with cell division. Together, these changes alter the balance between growth and lignification while also reducing biomass. LHY1 and LHY2 may also promote expression of BBX19 and BBX32, whose proteins appear to be part of the mechanism regulating timing of growth. Understanding clock regulation may be valuable for breeding projects targeting these important traits.